An Integrated Model for Locating-Routing in the Goods Delivery and Simultaneous Pickup in the Urban Context - Rodríguez Melquiades, José Antonio (2021)
Our gratitude to the Fondo Nacional de Desarrollo Científico, Tecnológico y de Innovación Tecnológica – FONDECYT.